PENGARUH PERMAINAN LOMPAT TALI TERHADAP KEMAMPUAN MOTORIK KASAR ANAK KELOMPOK B TK KARTIKA IV-9 RAIDER SURABAYA - Achmadi SPD; Luthfiyyatul Lailiyyah (WAHANA, 2018)
This event in the research will be based by a lack of motor abilities of the children when they have movement activities such as climbing, running, jumping, and while walking on the boards. This problems are caused by the students just learn to read, to write, and to calculate every day. The problem solving in this research is â€œThe Game of Jump Rope has Good Effect to Increase of the Abilities Motor for the Children Group B in Kindergarten Kartika IV-9 Raider Surabayaâ€. The type of this research is quantitative research. The purpose of this research is to know how the game of jump rope can involve the motor abilities for early childhood in kindergarten Kartika IV-9 Raider Surabaya. This research uses a type of Posttest-Only Control Group Design. The total population are 30 children that consist of 15 students asthe control groups and 15 students as experimental groups.The result of this research is used by t-test analysis that the game of jump rope can influence of the motor abilitiesfor children. This evident is that before being given treatment some children have less robustfor motorâ€™s skill. However, after being given the treatment, the children developed theirgood motor abilities. The children can do the body movement smoothly. They have good body movement. They donâ€™t be afraid to try the jump and their bodyto be came powerful and balanced. Keywords: game of jump rope, motor ability.